Investigation of CFRP prepreg tack for the first ply in automated fiber placement process - Nagarajan, Balakrishnan (2016)
Automated fiber placement process is a fast growing technique to manufacture aircraft structures with low material wastage, increased productivity and higher quality compared to hand layup. To meet the demands of increased productivity by using a multi mould tool and for better accessibility, the robot-based fiber placement units lay up the prepreg material on a vertically upright tool. However there is a risk that the prepreg starts slipping from the mould surface due to gravity if there is insufficient tack between the mould surface and first ply. This does not allow further placement of prepreg material. The bond strength between the tool and the first ply of the prepreg material must therefore be able to keep the prepreg intact to the metal mould surface. Furthermore it should withstand the entire weight of the subsequent prepreg layers laid on it. The influence of process parameters like compaction pressure, temperature and layup speed to make the first ply adhere to mould surface needs to be analysed.